Development of technologies for processing construction and demolition waste in the Republic of Moldova - Marian, Maria-Liliana; Jitari, Liliana (Technium Social Sciences Journal, 2025)
In the global context, characterized by accelerated urbanization, depletion of natural resources and worsening climate change, the construction sector plays a significant role in achieving sustainable development. In the context of issues related to ensuring sustainable development, one of the important directions is the problem of waste that persists in practically all areas of socio-economic life. Taking into account the importance of developing waste management in the construction sector, the development of technologies for processing construction and demolition waste will significantly reduce the amount of unprocessed waste, global CO2 emissions and will bring multiple benefits in terms of saving natural resources. This article addresses the situation regarding the main categories of waste, the main causes of construction and demolition waste generation, analyzing the main technologies for their processing, which, in the Republic of Moldova, are at an early stage of development. At the same time, the article analyzes the innovative solutions regarding the use of recycled materials in construction, demonstrating their role in promoting urban sustainability. The study examines the trends and innovative models, with the aim of showing how recycled materials can contribute to the development of green and sustainable cities.